2005
DOI: 10.1074/jbc.m509100200
|View full text |Cite
|
Sign up to set email alerts
|

Selective SecA Association with Signal Sequences in Ribosome-bound Nascent Chains

Abstract: The role of SecA in selecting bacterial proteins for export was examined using a heterologous system that lacks endogenous SecA and other bacterial proteins. This approach allowed us to assess the interaction of SecA with ribosome-bound photoreactive nascent chains in the absence of trigger factor, SecB, Ffh (the bacterial protein component of the signal recognition particle), and the SecYEG translocon in the bacterial plasma membrane. In the absence of membranes, SecA photocross-linked efficiently to nascent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 58 publications
0
22
1
Order By: Relevance
“…4 The incompatibility between the results obtained in vivo and in vitro suggests that any interaction between a novel factor and EspP SP is unstable in cell extracts. Biochemical studies have suggested that SecA can interact with signal peptides that have a highly basic N region at an early stage of translation (15,38), but because EspP(-6) SP (which contains an uncharged N region) promotes post-translational targeting, it does not appear likely that SecA recognizes EspP SP .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The incompatibility between the results obtained in vivo and in vitro suggests that any interaction between a novel factor and EspP SP is unstable in cell extracts. Biochemical studies have suggested that SecA can interact with signal peptides that have a highly basic N region at an early stage of translation (15,38), but because EspP(-6) SP (which contains an uncharged N region) promotes post-translational targeting, it does not appear likely that SecA recognizes EspP SP .…”
Section: Discussionmentioning
confidence: 99%
“…TF binding promotes posttranslational targeting, possibly by sterically hindering the docking of ribosomes onto the Sec complex (12)(13)(14). Recent evidence suggests that SecA, a cytoplasmic ATPase that plays a central role in the translocation reaction, may also bind to short nascent presecretory proteins (13,15). Other chaperones such as SecB bind to presecretory proteins late during translation or after translation is complete (16).…”
mentioning
confidence: 99%
“…The C-terminal domain is positioned in the middle of the molecule and provides the primary binding site for the nascent chain. The main contact of TF with the ribosome involves residues [44][45][46], located in the binding loop of the N-domain, and ribosomal protein L23 (6). The second contact involves ribosomal protein L29, which is not essential for TF-ribosome interaction (6).…”
mentioning
confidence: 99%
“…It is also interesting to note that the SecA mutation also resulted in the overproduction of 30S and 50S ribosomal proteins. The biological relevance of this observation is not clear considering that the binding of SecA to the L23 ribosomal protein seems to be the only interaction between this protein and the ribosome that has been described (68). Equally unclear is the apparent association of ribosomal proteins with the outer membrane fraction, a phenomenon we believe is not due solely to fraction contamination since we did not observe it when we used the same experimental approach to study the effect of iron on protein synthesis in the same A. baumannii strain (41).…”
Section: Discussionmentioning
confidence: 91%